An Undiagnosed Case of Chronic Pancreatitis With Multiple Visceral Arteries Pseudoaneurysm - Anwar, Muhammad Naveed (Cureus, 2021)
Visceral artery aneurysms, which could be either true or pseudo, are abnormal focal dilations of vessels supplying the abdominal organs. True aneurysms, by definition, suggest dilation of the vessel in response to increased blood flow, ultimately causing a blood-filled sac to form. Pseudoaneurysm, however, is the pooling of blood in surrounding tissues secondary to trauma or rupture. A 43-year-old woman G9 P9, known hypertensive was admitted electively for investigation of melena, hematemesis, hematochezia for one week along with weight loss and epigastric pain. Laboratory studies showed mild anemia with a hemoglobin level of 9.6 g/dL, hematocrit 29.5%, mean corpuscular hemoglobin (MCH) 26.7, upon which she was transfused two pints of blood and commenced at Injectable Vitamin K, injectable transamine, and infusion omeprazole. Two days later her levels improved to HB 12.4 g/dL, hematocrit 37.5%, MCH 26.7 pg, RBC 4.64 × 10*12/L. while being on treatment, a computed tomography (CT) mesenteric angiography was also conducted that showed multiple splanchnic pseudoaneurysms involving celiac axis trifurcation, gastroduodenal artery, superior/inferior pancreaticoduodenal artery, and jejunoileal branch of the superior mesenteric artery, and a large partially thrombosed pseudoaneurysm arising from superior pancreaticoduodenal branch causing significant mass effect on the second part of duodenum. On the basis of such findings, it was advised to perform coiling and embolization of the corresponding arteries. Multiple other small aneurysms with secondary arteriovenous malformations (AVM) were also seen. The whole circuit of flow retrograde and antegrade along with the aneurysm sac was blocked with multiple coils of variable sizes. An angiogram was repeated that revealed a good outcome. Pseudoaneurysms of the visceral arteries are very rare and affect mainly the splenic artery. The rarest of which is gastroduodenal artery (1.5%), pancreaticoduodenal artery (2%), and coeliac truck (4%). Therefore, this can be an incidental finding. The diagnosis is usually made with an angiography combined with clinical presentation. Variable treatment options are available depending on the patient’s fitness and hemodynamic stability. The endovascular approach, however, is mostly used in such cases.